Pengaruh Edukasi Media Kartu “KABAR JASA” Terhadap Perilaku Jajanan Sehat Anak Kelas IV Dan V di SDN Karangtengah III Dan SDN Plembon Gunungkidul - Zahidah, Nuril Aini; Badi'ah, Atik; Suryani, Eko; Mendri, Ni Ketut (Caring : Jurnal Keperawatan, 2024)
Food and nutrition affect the growth and development of school-age children. Children's snacking behavior to fulfill their nutritional needs depends on the surrounding environment. Many foods that are usually sold are still unsafe because they contain several contaminants that don’t fulfull the requirements of healthy snacks. For this reason, it’s necessary to educate about the selection of healthy snacks to develop snacking behavior. The media used for education is picture card game media. This study aims to know the effect of "KABAR JASA" card media education on healthy snacking behavior of fourth and fifth grade children at SDN Karangtengah III and SDN Plembon Gunungkidul. Type of research quasy experimental design with nonequivalent control group design. Research in 7 February – 8 March 2024. Sampling technique with total sampling. Data collection method with a questionnaire. The research subjects were 78 students consisting of IV and V classes. Statistical tests using Wilcoxon and Mann-Withey tests. The result is, in the experimental group with "KABAR JASA" card education, the good category increased from 14 students (35.9%) to 27 students (69.2%), the moderate category decreased from 25 students (53.8%) to 12 students (30.8%). The results of the Wilcoxon test in the experimental group p-value = 0.000 and in the control group p-value = 0.425. Mann Withney test results are p-value = 0.000. the conclusion of this research is "KABAR JASA" card media education have a significant effect on the healthy snacking behavior of fourth and fifth grade children at SDN Karangtengah III and SDN Plembon Gunungkidul.   Makanan dan nutrisi mempengaruhi tumbuh kembang anak usia sekolah. Perilaku jajanan anak untuk memenuhi kebutuhan nutrisinya tergantung lingkungan sekitar. Makanan yang biasanya dijual masih banyak yang kurang aman karena mengandung beberapa cemaran sehingga tidak memenuhi syarat jajanan sehat. Untuk itu, perlu dilakukan edukasi terkait pemilihan jajanan yang sehat agar terbentuk perilaku jajan yang sehat. Media yang digunakan untuk edukasi yaitu media permainan kartu bergambar. Penelitian ini betujuan untuk mengetahui pengaruh edukasi media kartu “KABAR JASA” terhadap perilaku jajanan sehat anak kelas IV dan V di SDN Karangtengah III dan SDN Plembon Gunungkidul. Penelitian dengan quasy experimental design with nonequivalent control group design. Dilaksanakan pada 7 Februari – 8 Maret 2024. Teknik sampling dengan total sampling. Metode pengambilan data dengan kuesioner. Subjek penelitian yaitu 78 siswa terdiri dari kelas IV dan V. Uji statistik menggunakan uji Wilcoxon dan Mann-Withey. Hasilnya yaitu kelompok eksperimen yang diberikan edukasi kartu “KABAR JASA” kategori perilaku baik meningkat dari 14 siswa (35,9%) menjadi 27 siswa (69,2%), kategori cukup menurun dari 25 siswa (53,8%) menjadi 12 siswa (30,8%). Hasil uji wilcoxon kelompok eksperimen p-value = 0,000 dan kelompok kontrol p-value = 0,425. Hasil uji Mann Withney yaitu p-value = 0,000. Kesimpulan dari penelitian ini yaitu ada pengaruh edukasi media kartu “KABAR JASA” terhadap perilaku jajanan sehat anak kelas IV dan V di SDN Karangtengah III dan SDN Plembon Gunungkidul.   Keywords: Kartu Bergambar, Kartu Kuartet, Perilaku, Jajanan Sehat